Firearm ownership and suicide: Has the time come to discuss uniformity of health and social assessments in aid of regulation? Reflection from a retrospective study on a forensic case series - Blandino, Alberto; Galante, Nicola; Cuppone, Fabio; Giriodi, Maddalena; Travaini, Guido Vittorio (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Firearm-related deaths are an issue of ongoing public interest, from a health and economic perspective. Worldwide, firearm prevalence in suicides varies widely, depending on multiple factors including the availability of weapons in each country. Although several studies have shown that national laws about gun ownership, reducing legal access to guns, decrease the risk of suicide by firearm, the current situation clashes with widely differing legislations. Study design. Retrospective study on a forensic case series. Methods. Autopsy reports assessed at the Section of Legal Medicine of Milan (Italy) from January 2014 to December 2023 were retrospectively documented. Only firearm suicides were considered. For each case, a close analysis of the criminal offence reports has been performed to obtain information about the gender and age of the victim, as well as the legal possession of firearms, psychiatric disorders, alcohol, and illicit drug abuse. Results. Among all the 1,164 suicides assessed at the Section of Legal Medicine of Milan over a 10-year-period, 101 cases (8.7%) were firearm-related. The male to female ratio was therefore about 13:1. No seasonal trends were observed. Most of the individuals owned the firearm license. Of the entire dataset, 35.6% suffered from psychiatric disorders, 4% of alcohol abuse and 2% of drug addiction. Among the owners of a firearm license, 42.3% had psychiatric disorders. Conclusions. Knowledge about firearm suicide and its relation to firearm legal possession is limited and current preventive laws should be reconsidered. Present administrative and clinical examinations required to obtain a firearm license in Italy and in some European territories are dealt with. The evaluation of the firearm-related risk of abuse is an essential but complex procedure, which requires not only clinic-anamnestic data but also in-deep psychiatric information. There is a need to develop and reinvigorate a debate that currently presents very heterogeneous solutions, but which would probably benefit from a common vision of the prevention strategies that can be implemented and enacted for the benefit of the entire community